Adapting HYDRUS‐1D to Simulate Overland Flow and Reactive Transport during Sheet Flow Deviations. Issue 6 (8th June 2017) - Liang, Jing; Bradford, Scott A.; Šimůnek, Jiří; Hartmann, Anne
Abstract : Core Ideas: HYDRUS‐1D code was adapted to solve the diffusion wave equation for overland flow. The modified code can simulate transport and fate of many different kinds of solute. The model can simulate physically nonequilibrium overland flow and transport processes. Surface runoff is commonly described in numerical models using either the diffusion wave or kinematic wave equations, which assume that surface runoff occurs as sheet flow with a uniform depth and velocity across the slope. In reality, overland water flow and transport processes are rarely uniform. Local soil topography, vegetation, and spatial soil heterogeneity control directions and magnitudes of water fluxes. These spatially varying surface characteristics can generate deviations from sheet flow such as physical nonequilibrium flow and transport processes that occur only on a limited fraction of the soil surface. In this study, we first adapted the HYDRUS‐1D model to solve the diffusion wave equation for overland flow at the soil surface. The numerical results obtained by the new model produced an excellent agreement with an analytical solution for the kinematic wave equation. Additional model tests further demonstrated the applicability of the adapted model to simulate the transport and fate of many different solutes (non‐adsorbing tracers, nutrients, pesticides, and microbes) that undergo equilibrium and/or kinetic sorption and desorption and first‐ or zero‐order reactions. HYDRUS‐1D includes a hierarchical series of models of increasing complexity to account for both uniform and physical nonequilibrium flow and transport, e.g., dual‐porosity and dual‐permeability models, up to a dual‐permeability model with immobile water. This same conceptualization was adapted to simulate physical nonequilibrium overland flow and transport at the soil surface. The developed model improves our ability to describe nonequilibrium overland flow and transport processes and our understanding of factors that cause this behavior.